Developing Basic Computer Programming Virtual Laboratory for Senior High School - Yan, Hsiao-Yuan; Xu, Zheng (International Journal of Educational Technology and Artificial Intelligence, 2023)
Recently, the Metaverse has emerged as a global focal point, drawing extensive attention thanks to rapid technological advancements. The forthcoming virtual reality promises amplified direct physical interactions, diminishing the significance of traditional constructs such as race, gender, and physical disabilities, ultimately offering profound societal advantages. Nonetheless, virtual reality development remains nascent, brimming with untapped potential. Despite proactive industry preparations and substantial investments, there’s a pressing need for expanded scholarly discourse on virtual reality to provide the scientific guidance necessary for its maturation. A basic Programming laboratory for Senior High School has been developed using the ASSURE learning development method, including six steps: Analyze Learners, State Objectives, Select Media and Materials, Utilize Media and Materials, Require Learner Participation, and evaluate and revise. The research finding shows that it can be implemented in the learning process of Basic Computer Programming subjects to increase student understanding.